2010
DOI: 10.1038/nature08918
|View full text |Cite
|
Sign up to set email alerts
|

Electron liquids and solids in one dimension

Abstract: Even though bulk metallic systems contain a very large number of strongly interacting electrons, their properties are well described within Landau's Fermi liquid theory of non-interacting quasiparticles. Although many higher-dimensional systems can be successfully understood on the basis of such non-interacting theories, this is not possible for one-dimensional systems. When confined to narrow channels, electron interaction gives rise to such exotic phenomena as spin-charge separation and the emergence of corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
208
2
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 224 publications
(218 citation statements)
references
References 74 publications
6
208
2
2
Order By: Relevance
“…It has been shown that at a critical density, a transition to a zigzag crystal takes place 7,11,23,25,26 . Though not for electrons, this zigzag transition has indeed been observed using 24 Mg + ions in a quadrupole storage ring 27 .…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…It has been shown that at a critical density, a transition to a zigzag crystal takes place 7,11,23,25,26 . Though not for electrons, this zigzag transition has indeed been observed using 24 Mg + ions in a quadrupole storage ring 27 .…”
Section: Introductionmentioning
confidence: 97%
“…Three equivalent minima at N = 58, N = 116, and N = 174 can be clearly seen. These minima correspond to configurations with defects in the outer-most rows, i.e., the outer rows have less particles than the inner rows, namely N inner = 12 (24,36), and N outer = 11 (22,33), respectively. The corresponding defect density is n 4.85 def = 1 − 11/12 = 0.083.…”
Section: A Defects In Five-and Six-row Crystalsmentioning
confidence: 99%
“…In recent years, a lot of the attention was devoted to 1D liquids with nonlinear dispersion [for reviews on this topic see Deshpande et al (2010); Imambekov et al (2012);and Matveev (2013) ]. In the TLL theory, the curvature of the quasiparticle spectrum is described by an irrelevant operator (in the renormalization group sense).…”
Section: Coulomb Drag Between Parallel Nanowiresmentioning
confidence: 99%
“…In the context of interacting 1D systems, it is well established that their low-energy equilibrium properties are described by the Luttinger liquid (LL) model [30][31][32]. They exhibit peculiar effects stemming from their non-Fermi liquid nature due to inter-particle interactions, such as charge and spin fractionalization [19,20,[32][33][34][35][36][37][38][39][40][41][42]. In recent years the LL model has also been proven to be a very powerful tool for studying the dynamics of 1D systems after a quench of the interaction strength.…”
Section: Introductionmentioning
confidence: 99%